The relevance of real-time data in estimating reaction functions for the Euro area - Dieter Gerdesmeier; Barbara Roffia (Hochschule für Bankwirtschaft (HfB), 2004)
This paper tackles the issue of the incompleteness of information available to the central bank when taking its monetary policy decisions. It is focused on euro area data and based on the simplistic assumption of the central bank following a simple monetary policy rule à-la-Taylor. Along the lines of the work by Orphanides (2001), our aim is to assess whether estimates of reaction functions which are carried out using revised data for the euro area can be misleading. In essence, the analysis yields indications which are consistent with the findings by Orphanides for the United States. First of all, the results found suggest that it would be preferable for a central bank not to attach too much weight on output gap measures in policy analysis, given that such measures are subject to large revisions over time. Moreover, the coefficients of a simple Taylor rule estimated in real time differ quite considerably from those related to the same rule estimated on the basis of ex post revised data. More precisely, a coefficient for inflation larger than one (which is a requirement for a unique equilibrium in many theoretical models) in real time is found only in case a forward-looking specification based on the Survey of Professional Forecasters is used. On the contrary, when using revised data, the same result is obtained if the Taylor rules include the current inflation rate. This shows how a misleading inference can occur when the appropriate available data are not taken into account.
urn:nbn:de:101:1-2008082178
Keywords: E58; F41; 330; Taylor rules; reaction functions; monetary policy; euro area; real-time data